2018
DOI: 10.1620/tjem.244.63
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Breast Cancer Risk According to Hormone Receptor Status in Japanese Women: A Case-Control Study

Abstract: Alcohol consumption is a risk factor for breast cancer in Western countries, but few studies have evaluated the risk for Japanese women, who have a relatively low alcohol intake. This case-control study investigated the association of alcohol consumption with breast cancer risk according to estrogen-receptor and progesterone-receptor (ER/PgR) status in Japanese women. From female patients aged 30 years and over admitted to a single hospital in Japan between 1997 and 2011, 1,256 breast cancer cases (669 ER+/ Pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The exposure variables related to alcohol consumption included history of alcohol drinking (never, ever, past, current), frequency of drinking per week (never, occasional or 1–2 times, 3–7 times), age at start of drinking (never, ≤20 years, ≥21 years), and amount of alcohol consumed per day (never, <5.0 g, ≥5.0 g). Although, in our previous case-control and cohort studies of breast cancer, the quantitative exposure variable had been classified based on finer categories [28, 29], the present study used the mid-point for variable categorization because of the limited number of patients. If necessary, analysis based on the finer categories was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure variables related to alcohol consumption included history of alcohol drinking (never, ever, past, current), frequency of drinking per week (never, occasional or 1–2 times, 3–7 times), age at start of drinking (never, ≤20 years, ≥21 years), and amount of alcohol consumed per day (never, <5.0 g, ≥5.0 g). Although, in our previous case-control and cohort studies of breast cancer, the quantitative exposure variable had been classified based on finer categories [28, 29], the present study used the mid-point for variable categorization because of the limited number of patients. If necessary, analysis based on the finer categories was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13] Associations between alcohol intake and breast cancer risk are also less clear among AYAs than in postmenopausal women. [14][15][16] Exercise and a plant-based diet are potentially protective against breast cancer among AYAs, as they are in older populations, although these studies are small. [17][18][19][20]…”
Section: Risk Factorsmentioning
confidence: 99%
“…Breast cancer is one of the most commonly diagnosed cancers affecting women in Taiwan, and its incidence rate is gradually increasing worldwide (7). The known risk factors for breast cancer are obesity (8), smoking (9), genetic mutations such as breast cancer susceptibility gene 1 (BRCA1) and breast cancer susceptibility gene2 (BRCA2) which are tumor suppressor genes (9,10), family history (11,12), alcohol consumption (11)(12)(13)(14), exposure to estrogen hormones over an extended period (11,14), diethylstilbestrol and postmenopausal hormone therapy (15,16). In addition, previous studies suggested that breast cancer can be attributed to exposure to radiofrequency radiation (17,18).…”
Section: Exposure To Radiofrequency Radiation Increases the Risk Of Bmentioning
confidence: 99%